Die Bürgschaft auf erstes Anfordern im deutschen und englischen Recht - Arnold, Stefan (Mohr Siebeck, 2008)
The first demand guarantee has been specifically designed to meet the essential commercial need for quick and reliable securities. Yet this liquidity function involves an immense potential for abuse. Stefan Arnold examines the dogmatic foundations on which English and German law overcome this conflict, and analyses the results they achieve.
PublicationDate: 20080208
Keywords: Kreditsicherungsrecht -- Kreditsicherung -- Bürgschaft -- Bürgschaftsrecht -- Englisches -- Bürgerliches Recht -- Handels- und Gesellschaftsrecht, Wirtschaftsrecht, Steuerrecht -- Internationales Privatrecht